2018
DOI: 10.1523/jneurosci.2835-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Monoamines Inhibit GABAergic Neurons in Ventrolateral Preoptic Area That Make Direct Synaptic Connections to Hypothalamic Arousal Neurons

Abstract: The hypothalamus plays an important role in the regulation of sleep/wakefulness states. While the ventrolateral preoptic nucleus (VLPO) plays a critical role in the initiation and maintenance of sleep, the lateral posterior part of the hypothalamus contains neuronal populations implicated in maintenance of arousal, including orexin-producing neurons (orexin neurons) in the lateral hypothalamic area (LHA) and histaminergic neurons in the tuberomammillary nucleus (TMN). During a search for neurons that make dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…Direct serotonergic input to orexin neurons might tonically inhibit orexin neurons during wakefulness states, constituting negative feedback regulation. We also confirmed that optogenetic activation of serotonergic fibers in the LH inhibited orexin neurons in vitro ( Saito et al, 2018 ). Although chemogenetic activation of 5-HT neurons in the DR showed minimal effects on activity of orexin neurons in vivo ( Saito et al, 2018 ), the physiological relevance of direct serotonergic influences on orexin neurons in the regulation of sleep/wakefulness states has been unclear.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Direct serotonergic input to orexin neurons might tonically inhibit orexin neurons during wakefulness states, constituting negative feedback regulation. We also confirmed that optogenetic activation of serotonergic fibers in the LH inhibited orexin neurons in vitro ( Saito et al, 2018 ). Although chemogenetic activation of 5-HT neurons in the DR showed minimal effects on activity of orexin neurons in vivo ( Saito et al, 2018 ), the physiological relevance of direct serotonergic influences on orexin neurons in the regulation of sleep/wakefulness states has been unclear.…”
Section: Discussionsupporting
confidence: 74%
“…Elucidation of the regulatory mechanisms of orexin neurons is important for understanding the physiological mechanisms of sleep/wakefulness control and the roles of orexin neurons in these functions. Orexin neurons receive innervations from many brain regions, including the limbic system, preoptic area, and monoaminergic neurons ( Sakurai et al, 2005 ; Yoshida et al, 2006 ; Saito et al, 2018 ). Among the factors that influence the activity of orexin neurons, serotonin (5-HT) was shown to strongly inhibit most orexin neurons through 5HT 1A receptors (5HT1ARs) ( Muraki et al, 2004 ; Tabuchi et al, 2014 ; Saito et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CSF-contacting nucleus receives input from the LH, PeF, and ZI and may participate in sleeping and arousal. Different neuron types in the tuberomammillary nucleus and LH are implicated in the sleep/wakefulness regulation (Saito et al, 2018). The PeF receives inputs from circadian rhythm messages of the SCh to promote waking (Zhong et al, 2017).…”
Section: Sleeping and Arousalmentioning
confidence: 99%